Building an International One Health Strain Level Database to Characterise the Epidemiology of AMR Threats: ESBL-AmpC Producing E. coli as An Example-Challenges and Perspectives - Perestrelo, Sara; Amaro, Ana; Brouwer, Michael S M; Clemente, Lurdes; Ribeiro Duarte, Ana Sofia; Kaesbohrer, Annemarie; Karpíšková, Renata; Lopez-Chavarrias, Vicente; Morris, Dearbháile; Prendergast, Deirdre; Pista, Angela; Silveira, Leonor; et al. (Antibiotics (Basel), 2023)
Antimicrobial resistance (AMR) is one of the top public health threats nowadays. Among the most important AMR pathogens, Escherichia coli resistant to extended spectrum cephalosporins (ESC-EC) is a perfect example of the One Health problem due to its global distribution in animal, human, and environmental sources and its resistant phenotype, derived from the carriage of plasmid-borne extended-spectrum and AmpC β-lactamases, which limits the choice of effective antimicrobial therapies. The epidemiology of ESC-EC infection is complex as a result of the multiple possible sources involved in its transmission, and its study would require databases ideally comprising information from animal (livestock, companion, wildlife), human, and environmental sources. Here, we present the steps taken to assemble a database with phenotypic and genetic information on 10,763 ESC-EC isolates retrieved from multiple sources provided by 13 partners located in eight European countries, in the frame of the DiSCoVeR Joint Research project funded by the One Health European Joint Programme (OH-EJP), along with its strengths and limitations. This database represents a first step to help in the assessment of different geographical and temporal trends and transmission dynamics in animals and humans. The work performed highlights aspects that should be considered in future international efforts, such as the one presented here.